2003
DOI: 10.1111/j.1475-6773.2003.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

County‐Level Income Inequality and Depression among Older Americans

Abstract: Objectives. To examine (1) whether county‐level income inequality is associated with depression among Americans aged 70 and older, taking into consideration county‐level mean household income and individual‐level socioeconomic status (SES), demographic characteristics, and physical health, and (2) whether income inequality effects are stronger among people with lower SES and physical health. Data Sources. The individual‐level data from the first wave of the Assets and Health Dynamics among the Oldest Old sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 46 publications
7
84
1
1
Order By: Relevance
“…Of the four studies in adolescents only, three found a significant association between income inequality and depression (two in the regression 23,26 and one in bivariate analysis only 28 ). Of the five studies in older adults only, three found an association between income inequality and depression (two in regression 19,22 and one in bivariate analysis only 27 ), one found no association 30 , and one found a negative association 35 . Participant ethnicity was reported in eight studies, with only three conducted in specific ethnic populations: in nearly 9,000 Hispanic adults aged 60 and older in Mexico 30 ; in nearly 6,500 Black and Hispanic adolescents in the US 7 ; and in Tsimane villagers in the Bolivian Amazon 17 .…”
Section: Associations Between Income Inequality and Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the four studies in adolescents only, three found a significant association between income inequality and depression (two in the regression 23,26 and one in bivariate analysis only 28 ). Of the five studies in older adults only, three found an association between income inequality and depression (two in regression 19,22 and one in bivariate analysis only 27 ), one found no association 30 , and one found a negative association 35 . Participant ethnicity was reported in eight studies, with only three conducted in specific ethnic populations: in nearly 9,000 Hispanic adults aged 60 and older in Mexico 30 ; in nearly 6,500 Black and Hispanic adolescents in the US 7 ; and in Tsimane villagers in the Bolivian Amazon 17 .…”
Section: Associations Between Income Inequality and Depressionmentioning
confidence: 99%
“…A number of studies were conducted in specific populations: five in older persons only 19,22,27,30,35 ; four in adolescents only 7,23,26,28 ; one in students aged 17-30 years 25 ; and one in low-income nursing assistants 21 .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eight articles reported results from multi-country studies 12,27,29,[31][32][33][34][35] ; ten studies were conducted in the USA 28,30,[36][37][38][39][40][41][42][43] ; three studies were carried out in the UK [44][45][46] ; two articles reported results from a study carried out in Brazil 47,48 ; one study was conducted in Australia 49 , one in Mexico 50 , one in Spain 51 , and one in South Africa 26 (Table 1).…”
Section: Figure 1 About Herementioning
confidence: 99%
“…One article included university students 35 , one included 11, 13 and 15-year-old students 31 and one sampled women with infant children 40 . Twenty-two articles assessed psychiatric diagnoses 12,[26][27][28][29][30]32,[34][35][36][37][39][40][41][42][43][44][45][46][47] , whereas three assessed psychological distress/symptoms or mental well-being/functioning 31,33,49 . One article assessed both psychiatric diagnosis and psychological symptoms 38 , and one article reported use of mental health services 48 .…”
Section: Table 1 About Herementioning
confidence: 99%
“…We selected individual covariates according to previous studies that focused on the effect of neighborhood characteristics on the psychological health of the elderly (36,37) and factors on SWB (4,38). As core covariates (39), we assessed age, sex, and years of education (dichotomized as ≥ 9 years or < 9 years).…”
Section: Individual-level Covariatesmentioning
confidence: 99%